2012
DOI: 10.4142/jvs.2012.13.2.187
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of a 0.0584% hydrocortisone aceponate spray on clinical signs and skin barrier function in dogs with atopic dermatitis

Abstract: The purpose of this study was to evaluate the effects of a topical spray containing 0.0584% hydrocortisone aceponate (HCA) on canine atopic dermatitis (CAD) and to evaluate the skin barrier function during the treatment of CAD. Twenty-one dogs that fulfilled the diagnostic criteria for CAD were included in this study. The HCA spray was applied once a day to the lesions of all dogs for 7 or 14 days. Clinical assessment was performed before (day 0) and after treatment (day 14), and clinical responses were correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…The numerical pruritus scale contained six categories of pruritic behaviour similar to that used in the validated PVAS10 method. 19,20 Lokivetmab administered at four week intervals was associated with decreases in the CADESI-04, pruritus and average TEWL values. When assessing response to treatment, it would seem reasonable to use the average TEWL calculated from several areas of the body given that a greater correlation is found in such cases.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The numerical pruritus scale contained six categories of pruritic behaviour similar to that used in the validated PVAS10 method. 19,20 Lokivetmab administered at four week intervals was associated with decreases in the CADESI-04, pruritus and average TEWL values. When assessing response to treatment, it would seem reasonable to use the average TEWL calculated from several areas of the body given that a greater correlation is found in such cases.…”
Section: Discussionmentioning
confidence: 92%
“…We decided to use this scale to simplify the assessment of pruritus by the owners. The numerical pruritus scale contained six categories of pruritic behaviour similar to that used in the validated PVAS10 method …”
Section: Discussionmentioning
confidence: 99%
“…Treatment duration and frequency of use should be tailored to each patient; applications should normally continue until complete and stable remission of signs (SOR C). Basis for the updated recommendations: In addition to the previously available clinical trial data, a small study confirmed that a one to two-week daily application of an hydrocortisone aceponate spray (Cortavance, Virbac) significantly improved lesions and pruritus in atopic dogs (QOE 2) [ 10 ]. A.3.b.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies have demonstrated that TEWL values decrease in remission during specific immunotherapy and non-specific anti-pruritus treatment (using cyclosporine) (Cornegliani et al 2012). A simultaneous decrease in CADESI and TEWL values during local treatment (using hydrocortisone aceponate and polyunsaturated fatty acids) was reported by Eui-Hwa Nam et al andTretter andMueller ( Tretter andMueller 2011, Nam et al 2012) The aim of the present study was the assessment of changes in transepidermal water loss in dogs treated with anti-pruritic drugs (cyclosporine A in a dose of 5 mg/kg BW).…”
Section: Introductionmentioning
confidence: 99%